Further consideration of the curvature of the Neandertal Femur. Issue 1 (11th October 2017) - Chapman, Tara; Sholukha, Victor; Semal, Patrick; Louryan, Stéphane; Van Sint Jan, Serge
Abstract: Objectives: Neandertal femora are particularly known for having a marked sagittal femoral curvature. This study examined femoral curvature in Neandertals in comparison to a modern human population from Belgium by the use of three‐dimensional (3D) quadric surfaces modeled from the bone surface. 3D models provide detailed information and enabled femoral curvature to be analyzed in conjunction with other morphological parameters. Materials and Methods: 3D models were created from CT scans of 75 modern human femora and 7 Neandertal femora. Quadric surfaces (QS) were created from the triangulated surface vertices in all areas of interest (neck, head, diaphyseal shaft, condyles) extracted from previously placed anatomical landmarks. The diaphyseal shaft was divided into five QS shapes and curvature was measured by degrees of difference between QS shapes. Each bone was placed in a local coordinate system enabling each bone to be analyzed in the same way. Results: The use of 3D quadric surface fitting allowed the distribution of curvature with similarly curved femora to be analyzed and the different patterns of curvature between the two groups to be determined. The Neandertals were shown to have a higher degree of femoral curvature and a more distal point of femoral curvature than the modern human population from Belgium. Conclusions: Morphological aspects of the Neandertal femur are different from this modern human population although mainly seem unrelated to femoral curvature. The relative lack of correlations with other femoral bony morphological factors suggests femoral curvature variations may be related to other aspects.